C++ Reactive Programming Design concurrent and asynchronous applications using the RxCpp library and Modern C++17 - Pai, Praseed (Packt Publishing Limited, 2018)
bLearn how to implement the reactive programming paradigm with C++ and build asynchronous and concurrent applications/bh2About This Book/h2ulliEfficiently exploit concurrency and parallelism in your programs/liliUse the Functional Reactive programming model to structure programs/liliUnderstand reactive GUI programming to make your own applications using Qt/li/ulh2Who This Book Is For/h2If you're a C++ developer interested in using reactive programming to build asynchronous and concurrent applications, you'll find this book extremely useful.